2009
DOI: 10.1007/s11069-009-9402-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of MM5 and WRF mesoscale model predictions of surface winds in a typhoon to planetary boundary layer parameterizations

Abstract: Sea surface winds and coastal winds, which have a significant influence on the ocean environment, are very difficult to predict. Although most planetary boundary layer (PBL) parameterizations have demonstrated the capability to represent many meteorological phenomena, little attention has been paid to the precise prediction of winds at the lowest PBL level. In this study, the ability to simulate sea winds of two widely used mesoscale models, fifth-generation mesoscale model (MM5) and weather research and forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
(6 reference statements)
6
25
0
Order By: Relevance
“…Hence, the number of vertical levels has been set to 40 in every domain. This number is similar to the number in the recent literature, which ranges between 30 and 46 (Miguez-Macho et al, 2004;Lo et al, 2008;Kwun et al, 2009;Santos-Alamillos et al, 2013;Etienne et al, 2013). The vertical resolution ensures that several eta levels lie below the PBL height at any time.…”
Section: Model Set-upsupporting
confidence: 82%
See 3 more Smart Citations
“…Hence, the number of vertical levels has been set to 40 in every domain. This number is similar to the number in the recent literature, which ranges between 30 and 46 (Miguez-Macho et al, 2004;Lo et al, 2008;Kwun et al, 2009;Santos-Alamillos et al, 2013;Etienne et al, 2013). The vertical resolution ensures that several eta levels lie below the PBL height at any time.…”
Section: Model Set-upsupporting
confidence: 82%
“…It employs an Eulerian mass-coordinate solver with a nonhydrostatic approach, and a terrain-following eta-coordinate system in the vertical. It is a state-of-the-art mesoscale model used in a variety of studies also for hindcast simulations (Kwun et al, 2009;Jiménez et al, 2010Awan et al, 2011;García-Díez et al, 2013;Jiménez and Dudhia, 2013;Santos-Alamillos et al, 2013;Menendez et al, 2014, among others). A first decision in regional climate modelling concerns the selection of the domain to be simulated.…”
Section: Model Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The vertical structure and spatial and temporal variability of the ABL are very important for numerical weather prediction (NWP). Many studies have demonstrated that many meteorological characteristics of the ABL can be represented by the MM5 and WRF mesoscale models (Kwun et al, 2009;Zhu, 2008;Miao et al, 2009). Furthermore, an accurate depiction of the meteorological conditions within the ABL is also important for air pollution modeling.…”
mentioning
confidence: 99%